A Systematic Review of Wordless Picture Book Interventions for Supporting Young Learners’ Second Language Skills - Muhammad Maghfur Fahrur Rozzi (Media Publikasi Cendekia Indonesia, 2025)
Wordless picture books (WPBs) are increasingly recognized as effective tools for enhancing reading comprehension and language acquisition among young learners in second language education. This study explores their integration into primary education settings, emphasizing their ability to foster creativity, develop narrative skills, and support vocabulary growth. By relying solely on illustrations, WPBs encourage learners to construct meaning, engage with visual cues, and interact with stories in open ended ways. The findings highlight diverse methodological approaches, including qualitative and quantitative studies, which reveal the potential of these books to promote bilingual literacy and reduce language barriers. Despite the promising potential of WPBs, significant gaps remain in the current literature, particularly in the areas of teacher perspectives, cultural adaptations, and the integration of modern technologies. Future research should specifically address these gaps. WPBs. Additionally, there is a need to investigate how emerging technologies, such as augmented reality (AR) or interactive digital platforms, can enhance the learning experience with WPBs. Focusing on these aspects will allow researchers to optimize the integration of WPBs in second language classrooms, making them more accessible and effective for a wide range of learners.